Find the value of $\sin\frac{2\pi}{7}+\sin\frac{4\pi}{7}+\sin\frac{8\pi}{7}$

My approach :

I used $\sin A +\sin B = 2\sin(A+B)/2\times\cos(A-B)/2 $

$\Rightarrow \sin\frac{2\pi}{7}+\sin\frac{4\pi}{7}+\sin\frac{8\pi}{7} = 2\sin(3\pi)/7\times\cos(\pi/7)+\sin(8\pi/7) $

$= 2\sin(3\pi)/7\times\cos(\pi/7)+\sin(\pi + \pi/7) $

$= 2\sin(3\pi)/7\times\cos(\pi/7)-\sin(\pi/7) $

I am not getting any clue how to proceed further or whether it is correct or not. Please help thanks..


You can evaluate this by using complex methods.

Let $\alpha=e^{2\pi i/7}$. Then $$\sin\frac{2\pi}{7}=\frac{\alpha-\alpha^{-1}}{2i}\ ,\quad \sin\frac{4\pi}{7}=\frac{\alpha^2-\alpha^{-2}}{2i}\ ,\quad \sin\frac{8\pi}{7}=\frac{\alpha^4-\alpha^{-4}}{2i}\ .$$ Now let $S$ be the sum of these three numbers. Write $S$ in terms of powers of $\alpha$ and calculate $S^2$. Initially it's a mess, but you can use the relations $$\alpha^7=1\quad\hbox{and}\quad \alpha^6+\alpha^5+\cdots+\alpha=-1$$ to show that it simplifies, amazingly, to $$S^2=\frac{7}{4}\ .$$ It's not hard to see that $S$ is positive, so $$S=\frac{\sqrt7}{2}\ .$$

Comment. You can also write the sum as $$S=\frac{1}{2i}\sum_{k=1}^6 \Bigl(\frac{k}{7}\Bigr)\alpha^k\ ,$$ where $(\frac{k}{7})$ is a Legendre symbol, and this connects the sum with some very interesting and often difficult mathematics.


The idea in this answer is: if you can introduce a trigonometric sum with arguments in arithmetic progression, then you have a nice formula that does all the job (see here for the statement and two proofs).


$$S=\sin \frac{2\pi}{7}+\sin \frac{4\pi}{7}+\sin \frac{8\pi}{7}$$


$$S^2=\sin^2 \frac{2\pi}{7}+\sin^2 \frac{4\pi}{7}+\sin^2 \frac{8\pi}{7}\\ +2\sin \frac{2\pi}{7}\sin \frac{4\pi}{7}+2\sin \frac{2\pi}{7}\sin \frac{8\pi}{7}+2\sin \frac{4\pi}{7}\sin \frac{8\pi}{7}$$

$$S^2=\frac{1-\cos \frac{4\pi}{7}}{2}+\frac{1-\cos \frac{8\pi}{7}}{2}+\frac{1-\cos \frac{16\pi}{7}}{2}+\cos \frac{2\pi}{7}-\cos \frac{6\pi}{7}\\ +\cos \frac{6\pi}{7}-\cos \frac{10\pi}{7}+\cos \frac{4\pi}{7}-\cos \frac{12\pi}{7}$$

$$S^2=\frac32+\cos \frac{2\pi}{7}+\frac12\cos \frac{4\pi}{7}-\frac12\cos \frac{8\pi}{7}-\cos \frac{10\pi}{7}-\cos \frac{12\pi}{7}-\frac12\cos \frac{16\pi}{7}$$

$$S^2=\frac32+\cos \frac{2\pi}{7}-\frac12\cos \frac{3\pi}{7}+\frac12\cos \frac{\pi}{7}+\cos \frac{3\pi}{7}-\cos \frac{2\pi}{7}-\frac12\cos \frac{2\pi}{7}$$

$$S^2=\frac32+\frac12\cos \frac{\pi}{7}-\frac12\cos \frac{2\pi}{7}+\frac12\cos \frac{3\pi}{7}$$

$$S^2=\frac32-\frac12\left(\cos \frac{2\pi}{7}+\cos \frac{4\pi}{7}+\cos \frac{6\pi}{7}\right)$$

And using the following formula from this answer, with $n=3, a=b=\frac{2\pi}{7}$:

$$\sum_{k=0}^{n-1} \cos (a+kb) = \frac{\sin \frac{nb}{2}}{\sin \frac{b}{2}} \cos \left( a+ (n-1)\frac{b}{2}\right)$$

$$\cos \frac{2\pi}{7}+\cos \frac{4\pi}{7}+\cos \frac{6\pi}{7}=\frac{\sin \frac{3\pi}{7}\cos \frac{4\pi}{7}}{\sin \frac{\pi}{7}}=\frac{\sin\frac{7\pi}{7}-\sin\frac{\pi}{7}}{2\sin\frac{\pi}{7}}=-\frac12$$



And we know that $S>0$ because the only negative term is $\sin\frac{8\pi}{7}=-\sin\frac{\pi}{7}$, and $0<\sin\frac{\pi}{7}<\sin\frac{2\pi}{7}$. So we have finally

$$\sin \frac{2\pi}{7}+\sin \frac{4\pi}{7}+\sin \frac{8\pi}{7}=\frac{\sqrt7}{2}$$


Here's my approach, it only use basic trigonometry identities (i.e, it requires no complex numbers), so it's quite lengthy. I would be glad if you guys can help me shorten it a bit.

  • Use Product to Sum Formula to prove that:

$\displaystyle \begin{align*}& \ \cos\left(\frac{2\pi}{7} \right) \cos\left(\frac{4\pi}{7} \right) + \cos\left(\frac{2\pi}{7} \right)\cos\left(\frac{8\pi}{7} \right) + \cos\left(\frac{4\pi}{7} \right)\cos\left(\frac{8\pi}{7} \right)\\ = & \ \cos\left(\frac{2\pi}{7} \right) + \cos\left(\frac{4\pi}{7} \right) + \cos\left(\frac{6\pi}{7} \right) \\ = & \ \cos\left(\frac{2\pi}{7} \right) + \cos\left(\frac{4\pi}{7} \right) + \cos\left(\frac{8\pi}{7} \right)\end{align*}$

  • Let $\displaystyle A = \cos\left(\frac{2\pi}{7} \right) + \cos\left(\frac{4\pi}{7} \right) + \cos\left(\frac{8\pi}{7} \right)$. Prove that $A < 0$, then square $A$ and using (1) along with Power Reduction Formula to prove that $A$ is a solution to the equation: $\displaystyle X^2 - \frac{5}{2}X - \frac{3}{2} = 0$. Hence $\displaystyle A = -\frac{1}{2}$.

  • Again use the Product to Sum Formula to prove that $\displaystyle \sin\left(\frac{2\pi}{7} \right) \sin\left(\frac{4\pi}{7} \right) + \sin\left(\frac{2\pi}{7} \right)\sin\left(\frac{8\pi}{7} \right) + \sin\left(\frac{4\pi}{7} \right)\sin\left(\frac{8\pi}{7} \right) = 0$.

  • Let $\displaystyle B = \sin\left(\frac{2\pi}{7} \right) + \sin\left(\frac{4\pi}{7} \right) + \sin\left(\frac{8\pi}{7} \right)$. Prove that $B > 0$. Using the result in (3), we have $\displaystyle B^2 = \sin^2\left(\frac{2\pi}{7} \right) + \sin^2\left(\frac{4\pi}{7} \right) + \sin^2\left(\frac{8\pi}{7} \right)$, using Power Reduction Formula, and (2), you'll get $\displaystyle B^2 = \frac{3}{2} - \frac{1}{2} A = \frac{7}{4}$. From the fact that $B > 0$, we'll have $\displaystyle B = \frac{\sqrt{7}}{2}$.

The above are just kind of hints, and you'll have to apply some trig formulae (identities) to get the result.


Setting $7\theta=\pi,S=\sin2\theta+\sin4\theta+\sin8\theta=(\sin2\theta+\sin8\theta)+\sin4\theta$

Using Prosthaphaeresis Formula & Double angle formula,


As $5\theta=\pi-2\theta,\sin5\theta=\sin2\theta$ and $3\theta=\pi-4\theta,\cos3\theta=-\cos4\theta$


Again using Prosthaphaeresis Formula, $S=2\sin2\theta(2\sin3\theta\sin\theta)$ which is clearly $>0$

But, $\sin2\theta=\sin(\pi-2\theta)=\sin5\theta;\sin\theta=\sin6\theta;\sin3\theta=\sin4\theta$

$\implies \dfrac S4=+\sqrt{\prod_{r=1}^6\sin r\theta}\ \ \ \ (1)$

We can derive (See below) $\sin7x=7\sin x+\cdots-64\sin^7x$

If $\sin7x=0,7x=n\pi$ where $n$ is any integer, $x=\dfrac{n\pi}7,0\le n\le6$

So, $\sin\dfrac{n\pi}7,0\le n\le6$ are the roots of $7\sin x+\cdots-64\sin^7x=0$

So, $\sin\dfrac{n\pi}7,1\le n\le6$ are the roots of $7+\cdots-64\sin^6x=0\iff64\sin^6x+\cdots-7=0$

Using Vieta's formula, $\prod_{r=1}^6\sin r\theta=\dfrac7{64}$

Apply this in $(1)$

Derivation $\#1:$

Using de Moivre's Theorem, $\cos7y+i\sin7y=(\cos y+i\sin y)^7$

$=\cdots +i\left(\sin^7y -\binom72\sin^5y\cos^2y+\binom74\sin^3y\cos^4y-\binom76\sin y\cos^6y\right)$

Writing $\cos^2y=1-\sin^2y$

$\cos7y+i\sin7y=\cdots +i\left(7\sin y-64\sin^7y\right)$

Derivation $\#2:$

Using Prosthaphaeresis Formula, $\sin7x+\sin x=2\sin4x\cos3x=2(2\sin2x\cos2x)(4\cos^3x-3\cos x)=4(2\sin x\cos x)(1-2\sin^2x)(4\cos^3x-3\cos x)$

$=8(\sin x-2\sin^3x)\cos^2x(4\cos^2x-1)$

$=8(\sin x-2\sin^3x)(1-\sin^2x)\{4(1-\sin^2x)-1\}$

$=8\sin x+\cdots-64\sin^7x$

$\implies\sin7x=7\sin x+\cdots-64\sin^7x$

  • $\begingroup$ Vieta formula gives the product as -7/64! $\endgroup$ – Ghartal Mar 3 at 10:31

Let $\Phi_7(x)$ the minimal polynomial of $\xi=\exp\left(\frac{2\pi i}{7}\right)$. Its Galois group over $\mathbb{Q}$ is cyclic and generated by $\xi\mapsto\xi^3$, since $3$ is a generator of $\mathbb{Z}/(7\mathbb{Z})^*$. The quadratic residues $\!\!\pmod{7}$ are $1,2,4$ and the quadratic non-residues are $3,5,6$, hence: $$ \alpha = \xi+\xi^2+\xi^4,\qquad \beta=\xi^3+\xi^5+\xi^6 $$ are two conjugated algebraic numbers with degree $\frac{6}{3}=2$.
In particular, both $\alpha+\beta$ and $\alpha\beta$ are rational numbers: $$ \alpha+\beta=\sum_{k=1}^{6}\xi^k=-1,\qquad \alpha\beta=3+\sum_{k=1}^{6}\xi^k=2 $$ and the minimal polynomial of $\alpha$ and $\beta$ is given by $x^2+x+2$. It is straightforward to check that $\text{Im}(\alpha)>0$ and $\text{Im}(\beta)<0$, hence by computing the discriminant of $x^2+x+2$ we have: $$ \alpha-\beta = \sqrt{-7} $$ and the claim follows by De Moivre's formula, since, for instance, $$ \xi-\xi^6 = \exp\left(\frac{2\pi i}{7}\right)-\exp\left(-\frac{2\pi i}{7}\right)=2i\sin\left(\frac{2\pi}{7}\right).$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.